Internationalization, Innovation and Sustainability of MNCs in Latin America - Liberman, L.; Liberman, L.; Newburry, W.; Newburry, W. (AIB Latin America, 2013)
Presents research findings and theoretical developments in the International Business field, with special emphasis on the issues of internationalization, innovation and sustainability in Latin America.